A study on the factors that contribute to the work-family conflict at PNB / Nurul Diyana Mohamed Noor - Mohamed Noor, Nurul Diyana (2011)
Work–family conflict is a type of inter-role conflict that occurs as a result of incompatible role pressures from the work and family domains. Work role characteristics that are associated with work demands refer to pressures arising from excessive workload and time pressures. The purpose of this research is to identify the factors that contribute to the work-family conflict. There are three factors that researcher focus which is role overload, management support and also gender role orientation. The results of the study imply that work-family conflict is an important concern for individuals and organizations alike because of its negative consequences leading to reduced job performance as well as family satisfaction and hence to reduced life satisfaction.